2017
DOI: 10.3390/w9020083
|View full text |Cite
|
Sign up to set email alerts
|

Water Savings of Crop Redistribution in the United States

Abstract: Demographic growth, changes in diet, and reliance on first-generation biofuels are increasing the human demand for agricultural products, thereby enhancing the human pressure on global freshwater resources. Recent research on the food-water nexus has highlighted how some major agricultural regions of the world lack the water resources required to sustain current growth trends in crop production. To meet the increasing need for agricultural commodities with limited water resources, the water use efficiency of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 25 publications
2
29
0
Order By: Relevance
“…At the same time, however, results show that IWR c values for corn were significantly higher than those for the other major crops; thus, a rapid expansion in the area of cultivated corn would only serve to intensify the water supply imbalance [44]. We argue that a continuous increase in the area of cultivated corn is not feasible; rather, it is crucial to minimize the cultivation of water-intensive crops and the expansion of cultivated land, emphasizing instead the husbandry of plants that require less water [45,58,59]. …”
Section: Policy Implicationsmentioning
confidence: 83%
“…At the same time, however, results show that IWR c values for corn were significantly higher than those for the other major crops; thus, a rapid expansion in the area of cultivated corn would only serve to intensify the water supply imbalance [44]. We argue that a continuous increase in the area of cultivated corn is not feasible; rather, it is crucial to minimize the cultivation of water-intensive crops and the expansion of cultivated land, emphasizing instead the husbandry of plants that require less water [45,58,59]. …”
Section: Policy Implicationsmentioning
confidence: 83%
“…This analysis (Falkenmark & Rockström, ) did not entirely account for the increasing water demand associated with dietary transitions or growing biofuel demand. Nevertheless, it stressed the important constraints placed by water resources on global food security and the need for approaches that conserve water or use it more efficiently (Davis, Rulli, Garrassino, et al, ; Davis, Rulli, Seveso, et al, ; Davis, Seveso, et al, ; Jägermeyr et al, ; MacDonald et al, ) instead of increasing human appropriation of water resources by expanding agriculture (i.e., green water use) or increasing withdrawals for irrigation (i.e., blue water use).…”
Section: Food‐water Nexusmentioning
confidence: 99%
“…Likewise, it is possible to use different irrigation and soil management strategies to close the crop yield gap by one half without increasing cropland area or irrigation use (Jägermeyr et al, ). Other work showed that, by redistributing crops on the basis of their suitability, it is possible for the United States to realize a modest water savings (5%) and improve calorie (+46%) and protein (+34%) production without adversely impacting feed production, crop diversity, or economic value (Davis, Seveso, et al, ). Similarly, recent research investigating global scenarios of crop redistribution to minimize irrigation water consumption has shown that it is possible to increase food production and feed an additional 825 million people while reducing irrigation water consumption by 12% without losing crop diversity or expanding the cultivated area (Davis, Rulli, Seveso, & D'Odorico, ).…”
Section: A Look Into the Futurementioning
confidence: 99%
“…Thirteen of the fourteen papers in this special issue consider green and blue WFs [14][15][16][17][18][19][20][21][22][23][24][25][26], while eight papers include grey WF estimation. All papers that include the grey WF specifically focus on pollution through nitrogen [14,15,17,19,21,22,25,27].…”
Section: The Papers In This Special Issue: Measuring Efficiency and Smentioning
confidence: 99%
“…Davis et al [24] study the option of increasing water-use efficiency through changing the spatial crop production pattern. They analyze, for the case of the United States, how consumptive water footprints can be reduced by changing where what crops are grown while making sure that current levels of calorie and protein production and income are maintained, and while staying within the currently cultivated land.…”
Section: The Papers In This Special Issue: Measuring Efficiency and Smentioning
confidence: 99%